EVALUASI PELAKSANAAN KEBIJAKAN PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN (PUAP) DI KECAMATAN BATANG KABUPATEN BATANG - Nisma Okidah; Budi Setiyono; Turtiantoro . (Journal of Politic and Government Studies, 2015)
Study on Evaluation of Rural Agribusiness Development Policy (PUAP) in the District of Batang, Batang county is a fairly interesting discussion in line with the policies of poverty alleviation in rural areas.Developing countries such as Indonesia have major problems, namely poverty and unemployment, especially in rural areas. Therefore, the Ministry of Agriculture of the Republic of Indonesia issued Regulation of the Minister of Agriculture No. 16 / Permentan / OT.140 / 2/2008 on February 11, 2008 on general guidelines for Rural Agribusiness Development (PUAP) to overcome the limitation of capital sources for farmers. In the framework of the implementation of PUAP Minister of Agriculture has established a Rural Agribusiness Development Team of the Minister of Agriculture No. 545 / Kpts / OT.160 / 9/2007. Batang district is the recipient of funds. In the implementation of the Rural Agribusiness Development Policy (PUAP) also implemented by the Denasri Wetan sub district, Kasepuhan sub district, and Sambong sub district. The activities of the Rural Agribusiness Development Policy (PUAP) are savings and loans. Therefore, the formulation of the problem in this research is